Efficacy of home-based and inpatient treatment for children and adolescents in psychiatric crisis: A systematic review protocol - Karolina Foremnik; Gaby Sroczynski; Jan Stratil; Anja Neumann; Barbara Buchberger (PLoS ONE, 2025)
Purpose Children and adolescents experiencing psychiatric crises often undergo inpatient treatment, which may limit family involvement, stigmatize young individuals, and impede the application of therapeutic outcomes in their daily lives. This situation can result in increased rates of rehospitalization, the development of chronic conditions, and prolonged hospital stays. Home-based treatment represents a potential alternative to traditional inpatient care. The objective of the planned systematic review is to provide a comprehensive comparison of the effectiveness and cost-effectiveness of inpatient and home-based treatment modalities, with a particular focus on primary outcome parameters such as psychopathology, family functioning, and social functioning. Furthermore, secondary outcomes, including rates of relapses and rehospitalizations, will be evaluated. Methods The systematic search will be conducted using Medline, Embase, PsycInfo and Cochrane databases, following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The included studies will undergo a rigorous quality assessment using the Cochrane Risk of Bias (RoB2) tool for randomized trials and the Risk of Bias in Non-randomized Studies - of Interventions (ROBINS-I) tool for non-randomized studies. Where appropriate, data will be synthesized by meta-analysis using R-Studio and supplemented by sensitivity analyses to assess the robustness of the results. The overall quality of the evidence is assessed using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) framework. Discussion The planned systematic literature review will provide a synthesis of the current state of research on the comparative effectiveness of both treatment modalities. The objective is to furnish information for the delivery of effective patient care that also represents a cost-efficient solution for the healthcare system. Systematic review registration This review protocol has been registered with the International Prospective Register of Systematic Reviews (PROSPERO) under the registration number CRD42023458888.